Expression and Localization of a New Parvovirus-Derived Protein in the Guinea Pig - Camila E. Osega; Fernando J. Bustos; Francisca C. Bronfman; Robert J. Gifford; Gloria Arriagada (Viruses)
Endogenous viral elements (EVEs) are genomic sequences derived from viruses. Some EVEs have open reading frames (ORFs) that can express co-opted proteins in their host. Furthermore, some EVEs that are expressed as proteins have become part of cellular genes that are fusions of hosts and EVE sequences. Endogenous parvoviral elements (EPVs) are highly represented in mammalian genomes, and some of them contain ORFs and can be expressed as proteins. We have shown that an EPV containing an ORF is part of the guinea pig gene enRep-M9l. This gene is broadly transcribed in vivo, indicating that it can be translated into a protein. By generating antibodies against the enRep coding sequence of the enRep-M9l ORF, we showed that the protein enRep-M9l is expressed in vivo and in the guinea pig-derived cell line JH4. By immunofluorescence and in situ proximity ligation assays, we observed that enRep-M9l protein has a cytoplasmic localization near microtubules. The results of this study suggest that the guinea pig EPV-derived protein enRep-M9l is a microtubule-associated protein. To our knowledge, this is the second demonstration that an EPV-derived protein is expressed in vivo.